CRLH-Transmission Line for Design and Analysis of Compact Microstrip Patch Antenna - Kr Kaushik, Awanish; Kumar, Anubhav; L. Yadava, R. (International Journal of Engineering and Technology, 2018)
The composite right/left-hand transmission line is displayed as an ordinary Transmission Line having two type of properties, first one left-hand properties and second one right-hand properties. By demonstrating a metamaterial based CRLH as a comparing TL, TL hypothesis can be utilized for analysis and plan one-, two-, or even three-dimensional CRLH metamaterials. The structure of CRLH-TL has the arrangement of metamaterial transmission line (TL) made out clearly by composite right-/left-hand (CRLH) unit cells. The Composite Right Left Handed (CRLH) transmission lines are on recent displayed as a kind of artificial transmission lines with various microwave applications. This examination take a gander at various types of execution of these transmission lines and the impact over the execution. The examination is passed on utilizing both lumped parts and microstrip utilization of the unit cells. As a summed up, show for CRLH TL provides for an incredible level of excellent stage reaction, for instance, double band task, nonlinear frequency, bandwidth capacity upgrade, and furthermore the presence of basic frequency with zero phase velocity. In this paper, we discuss about a Microstrip Patch antenna which is based on composite right/left-hand transmission line.Â Â Â